Grassroots Innovation Movements - Smith, Adrian (Pathways to Sustainability, 2017)
Innovation is increasingly invoked by policy elites and business leaders as vital for tackling global challenges like sustainable development. Often overlooked, however, is the fact that networks of community groups, activists, and researchers have been innovating grassroots solutions for social justice and environmental sustainability for decades. Unencumbered by disciplinary boundaries, policy silos, or institutional logics, these 'grassroots innovation movements' identify issues and questions neglected by formal science, technology and innovation organizations. Grassroots solutions arise in unconventional settings through unusual combinations of people, ideas and tools. This book examines six diverse grassroots innovation movements in India, South America and Europe, situating them in their particular dynamic historical contexts. Analysis explains why each movement frames innovation and development differently, resulting in a variety of strategies. The book explores the spaces where each of these movements have grown, or attempted to do so. It critically examines the pathways they have developed for grassroots innovation and the challenges and limitations confronting their approaches. With mounting pressure for social justice in an increasingly unequal world, policy makers are exploring how to foster more inclusive innovation. In this context grassroots experiences take on added significance. This book provides timely and relevant ideas, analysis and recommendations for activists, policy-makers, students and scholars interested in encounters between innovation, development and social movements.